2012
DOI: 10.3102/0162373712443307
|View full text |Cite
|
Sign up to set email alerts
|

What Do the California Standards Test Results Reveal About the Movement Toward Eighth-Grade Algebra for All?

Abstract: In California, an increasing number of 8th graders have taken algebra courses since 2003. This study examines students ' California Standards Test (CST) results in grades 7 through 11, aiming to reveal who took the CST for Algebra I in 8th grade and whether the increase has led to a rise in students' taking higher-level mathematics CSTs and an improved performance in following years. Results show that the pipeline of 8th-grade algebra and following years' higher-level mathematics CSTs has a significant leak i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…We estimate that one-third of remaining accelerated students return to the non-accelerated track each year, so that the initial impact of acceleration on coursework decays over time. This leaky pipeline is consistent with evidence from California's eighth grade algebra push (Liang et al, 2012) and from other North Carolina districts (Clotfelter et al, 2015). We complement prior research focused on test scores and course grades by emphasizing students' coursework trajectories, given increasing quasi-experimental evidence that improved high school math coursework can have substantial effects on high school graduation rates, college enrollment rates and labor market earnings, both for relatively low-skilled students (Goodman, 2012;Cortes et al, 2015) and relatively high-skilled ones (Joensen and Nielsen, 2009;Jackson, 2010;Smith et al, 2015).…”
Section: Introductionsupporting
confidence: 73%
“…We estimate that one-third of remaining accelerated students return to the non-accelerated track each year, so that the initial impact of acceleration on coursework decays over time. This leaky pipeline is consistent with evidence from California's eighth grade algebra push (Liang et al, 2012) and from other North Carolina districts (Clotfelter et al, 2015). We complement prior research focused on test scores and course grades by emphasizing students' coursework trajectories, given increasing quasi-experimental evidence that improved high school math coursework can have substantial effects on high school graduation rates, college enrollment rates and labor market earnings, both for relatively low-skilled students (Goodman, 2012;Cortes et al, 2015) and relatively high-skilled ones (Joensen and Nielsen, 2009;Jackson, 2010;Smith et al, 2015).…”
Section: Introductionsupporting
confidence: 73%
“…Outcomes, unfortunately, are mixed at best. Take, for example, the broad movement across states to require algebra for all students in eighth grade (e.g., see Liang, Heckman, & Abedi, , for a discussion of California; see Best, , for a discussion of Wisconsin). The hope is that by accelerating students’ mathematics tracks, we will get more of them into the STEM pipeline.…”
Section: Critiques and Limitations Of The Pipeline Metaphormentioning
confidence: 99%
“…Our study, and many others, has shown that placing all 8th-grade students into algebra courses does not help all of them in their subsequent year's of learning (Clotfelter, Ladd, & Vigdor, 2012;Liang, Heckman, & Abedi, 2012;Loveless, 2008;Taylor, 2011;Waterman, 2010;Williams, Haertel, Kirst, Rosin, & Perry 2011;. Our study also indicates that students who scored below proficient on the CST for Algebra I at 8th grade have a 69% less chance to score proficient or above on their CST for Algebra I at 9th grade compared to their peers who scored proficient or above on the CST for General Mathematics at 8th grade.…”
Section: Discussionmentioning
confidence: 46%
“…This paper then aims to provide empirical evidence in two critical elements of algebra success for all: student placement and algebra preparation. We make use of our most recent studies to answer three questions (Liang, 2009;Liang, Heckman, & Abedi, 2012). First, regarding both placement and preparation, we looked at whether the increase in the number of California 8thgrade students taking algebra has achieved the goal of the "algebra for all" policy, namely, increasing the overall college preparation course-taking pipeline.…”
Section: Two Elements Of Algebra Success: Placement and Preparationmentioning
confidence: 99%